1967
DOI: 10.1121/1.1910662
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Properties of Sediments

Abstract: This is a summary of an experimental study to measure the acoustic properties of water-saturated sediments. The sediments used were laboratory prepared to allow control of physical parameters (such as grain size, volume concentration, compressibility, etc.) and to approximate natural sediments. Acoustic velocity and attenuation in the sediments were measured over the frequency range 4–600 kHz. Acoustic measurements were made at high frequencies by means of two probes inserted in the sediments, and at low frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…This might have been a consequence of flocculation or settling, or both. The measured attenuations increase to about 10% concentration, when they level off and then begin to decrease, and thus it is inferred by Hampton (1967) that particle interactions begin to be significant at ¢ = 0.10. Urick (1947Urick ( ,1948 presented similar measurements of velocity and attenuation for a kaolinite suspension at a frequency of 1 MHz, and the attenuation and velocity display the same variations as a function of concentration as the 100 kHz data.…”
Section: Comparisons To Laboratory Datamentioning
confidence: 93%
See 3 more Smart Citations
“…This might have been a consequence of flocculation or settling, or both. The measured attenuations increase to about 10% concentration, when they level off and then begin to decrease, and thus it is inferred by Hampton (1967) that particle interactions begin to be significant at ¢ = 0.10. Urick (1947Urick ( ,1948 presented similar measurements of velocity and attenuation for a kaolinite suspension at a frequency of 1 MHz, and the attenuation and velocity display the same variations as a function of concentration as the 100 kHz data.…”
Section: Comparisons To Laboratory Datamentioning
confidence: 93%
“…Kuster and Toksiiz (1974b) concluded that anelasticity of the polystyrene spheres made a significant contribution to the attenuation in the suspensions, and it is possible that the neglect of this factor does cause some of the error in the theoretical predictions. Hampton (1967) presented a summary of a fairly large amount of data from laboratory measurements in sediments containing water. Included was a set of measurements of velocity and attenuation in suspensions of kaolinite clays of varying concentration at 100 kHz.…”
Section: Comparisons To Laboratory Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments in which the viscous losses are significant were carried out by Hampton (1967), but those were for clay particles which are highly non-spherical. To assess the theory for the viscous regime, we have measured attenuation for a suspension of small glass particles in water.…”
Section: Comparison With Experimentsmentioning
confidence: 99%